A Potential Tumor Suppressor Gene Named miR-508-5p Inhibited the Proliferation and Invasion of Human Melanoma Cells by Targeting KIT. (30th September 2020) - Dang, Lin; Wang, Yan; Shi, Cuiping; Liao, Mengsi; Sun, Zhaojun; Fang, Sining
Melanoma is the main death cause of human skin cancer. Increasing evidences demonstrate that microRNAs act as key roles in mediating tumor occurrence and progression. MiR-508-5p has proved to participate in the development of various types of human malignancies. However, the role of miR-508-5p in melanoma remained unclear. In in vitro study, miR-508-5p level in peripheral blood samples of patients with melanoma and human melanoma A375 cells was downregulated compared to that in normal peripheral blood samples or normal human epidermal melanocytes (MHEM). MiR-508-5p overexpression significantly inhibited the cell proliferation, migration and invasion in A375 cells, and thus inhibiting KIT expression at both gene and protein levels. Furthermore, western blot analysis showed miR-508-5p reduced cell proliferation by targeting KIT to modulate RAS/RAF/MEK/ERK pathway. Taken together, we speculated that miR-508-5p functioned as an important suppressor in human melanoma by targeting KIT, suggesting miR-508-5p might be a promising tumor suppressor gene for further target therapies from bench to clinic.